Journal The Perspective of The Demographic Revolution To Human Capital Achieve Sustainable Development For Companies In Indonesia - Sitohang, Nahason (Green Publisher Indonesia, 2022)
This paper tries to examine Human Capital from the perspective of Demographic Reformation with various shifts in various demographic variables in it causing demographic transitions in various countries in the world each have different characteristics. Demographic revolution and Human Capital are an inseparable part in terms of Economic Development, Sustainable Social The Asia Pacific for Human Development perspective has an orientation to eliminate poverty, poverty for all mankind, not only that, sustainable development is expected to be able to provide a better life for efforts meeting the needs of society today and for the future wisely there for all mankind in a fair and equitable manner. Sustainable development is an effort to design a new economic, social development model where Human Capital in sustainable development is a capital asset for companies/organizations, able to open up new business opportunities, new jobs for the benefit of an environmentally friendly demographic bonus.